Impact of Work Environment on Job Satisfaction: A Case of School Teachers - Maharjan, Rishma; Bhandari, Dadhi Ram (Nepalese Journal of Business and Management Studies, 2022)
Work environment refers to the elements that comprise the setting in which employees work. This research explained two factors of working environment namely working conditions, and job safety and security. As per the various study, if the employees are highly satisfied with their job, it tends to achieve the higher productivity in the organization. So, this study aims to examine factors influencing the job satisfaction of school teachers. Two factor theory is the theoretical foundation for the study. Data were collected utilizing the structured questionnaire which was distributed among 121 school teachers out of which 98 school teachers represents the sample size. The study employed descriptive, relational and casual research designs. Various descriptive and inferential statistical tools like correlation and regression were utilized for data analysis. The findings revealed that working condition, and job safety and security have significant effect on job satisfaction among school teachers and among these two, job safety and security is the most important factor for job satisfaction of the school teachers in Dallu area under study.